Drosophila strain specific response to cisplatin neurotoxicity - Christopher M. Groen; Jewel L. Podratz; Kevin Treb; Anthony J. Windebank (Fly, 2018)
Drosophila melanogaster has recently been developed as a simple, in vivo, genetic model of chemotherapy-induced peripheral neuropathy. Flies treated with the chemotherapy agent cisplatin display both a neurodegenerative phenotype and cell death in rapidly dividing follicles, mimicking the cell specific responses seen in humans. Cisplatin induces climbing deficiencies and loss of fertility in a dose dependent manner. Drosophila sensitivity to cisplatin in both cell types is affected by genetic background. We show that mutation or RNAi-based knockdown of genes known to be associated with CIPN incidence in humans affect sensitivity of flies to CIPN. Drosophila is a promising model with which to study the effect of genetics on sensitivity to CIPN.